The Geographic Factors-Based Optimization of National Flight Hub Airport Locations for Enhances Aviation Safety Standard - Dwi Lestary; Dhian Supardam; Ocky Soelistyo Pribadi; Direstu Amalia (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2024)
Indonesia's strategic geographical location and conditions are a result of its archipelagic status. Indeed, this significantly impacts the livelihoods of Indonesians, particularly in the area of transportation. In order to facilitate the mobility of individuals between islands, the government constructed transportation infrastructure and facilities. This will serve as a reference for government regulations that aim to reduce inequality, specifically in the development and distribution of products and services outside Java, particularly in Papua. The primary objective of this research is to conduct a connectivity analysis as an initial step towards optimizing the transportation network and determining the level of connectivity between Indonesian provinces through air transportation. Next, the researchers will study the existing air transportation network's structure to understand its characteristics clearly. It will be helpful material for formulating optimization and network management scenarios. The structuring pattern in question is the application of the hub-and-spoke network concept. The hub-and-spoke network pattern focuses on optimization problems from the perspective of economies of scale. The researchers optimized the provincial capital airport's location to establish a hub airport and subsequently refined the analysis results to enhance the efficiency of the new flight service network. The above steps will compare air travel performance before and after the network arrangement scenario. Indicators for the network connectivity level will also be present, indicating that the final product optimization is now ready for verification. The target of this research is to produce a concept or optimize the location of airport hubs through a comprehensive study taking into account geographic factors and conducting an analysis of the location of National Aviation Hub airports, which is the novelty of this research.